Approaches to crisis-preventing and conflict-sensitive development cooperation - Stefan Klingebiel (Deutsches Institut für Entwicklungspolitik (DIE), 2001)
Every year violent disputes occur in the form of domestic and international conflicts in 30 to 50 countries. The attacks of 11 September 2001 have also revealed the dangers of extreme forms of terrorism. Development policy must react both to symptoms of crisis and conflict and to terrorism.The area of crisis prevention and conflict management has become firmly established in development cooperation in recent years. It is not an innovation dictated by fashion, but a necessary extension.One important empirical conclusion is that development cooperation has an intended and unintended influence on conflicts. Although the options open to development cooperation for bringing constructive influence to bear should not be overestimated, some are certainly worth considering. Development cooperation can help to remove the causes of conflicts and to create opportunities for non-violent conflict resolution. Suitable country strategies (with account taken of the potential for conflict, etc.), conflict impact assessments and specific measures (such as peacepromoting projects in the education and media sectors) may help in this respect. Practical conflict-sensitive development cooperation is, however, still in its infancy.Coherent interaction between development cooperation and other policies (especially foreign policy) is very important and should be more easily recognizable in practice. Crisis prevention and conflict management are important tasks for policy as a whole.The contribution that development policy may make to the fight against terrorism is a new and extremely difficult challenge. Above all, development cooperation may help to deprive terrorist groups of their breeding ground by removing the structural causes of conflict and to increase the legitimacy of government structures and their ability to funktion.
Keywords: 330